Sinkronisasi UU ITE dan UU Kepariwisataan dalam Pengawasan Promosi Pariwisata Digital di Indonesia - Rizqy Prasetyani Putri; Shinta Pramesti Kartika Hadist; Suryana Hasbas (Tamasya : Jurnal Pariwisata Indonesia, 2025)
Digital transformation has transformed the tourism promotion landscape through social media, travel marketplaces, and user-experience-based content. Visual, interactive, and rapidly disseminating digital information shapes destination images and influences traveler decisions. However, the lack of digital promotion standards allows for misleading promotional practices, visual manipulation, false testimonials, and exaggerated claims that have the potential to harm tourism consumers. This study aims to analyze the synchronization between the Electronic Information and Transactions Law (UU ITE) and the Tourism Law in overseeing digital tourism promotion. This study uses a normative juridical method with a legislative approach and a literature review of academic documents and related news. The research findings show that while both laws share the same goal of ensuring accurate and non-misleading information, neither provides specific technical standards for digital promotion. The ITE Law is general and does not specifically regulate tourism promotion, while the Tourism Law was drafted before social media became a primary tool for destination marketing. This has resulted in regulatory gaps and fragmented authority between the Ministry of Communication and Informatics, the Ministry of Tourism and Creative Economy, BPKN, and BPSK. This research recommends the establishment of derivative regulations related to digital promotion, ethical content standards, advertising transparency, and an integrated cross-agency oversight mechanism to protect tourism consumers in the digital space.